Computation of quantum‐corrected noise in graphene‐SiC‐based impact avalanche transit time diode. (10th March 2020) - Ghivela, Girish C.; Sengupta, Joydeep
Abstract: Here, we have performed the noise analysis in graphene‐SiC‐based double drift region impact avalanche transit time diode (IMPATT). For computation, the noise model taken is based on drift diffusion with quantum corrections. Though noise computation in IMPATT with classical drift diffusion model are widely followed in earlier years, noise analysis through classical drift diffusion model is independent of confinement and tunneling due to quantum effects. Noise computed through quantum‐corrected noise model is more accurate to measured noise. Therefore, by considering quantum effects in addition to classical noise model, we have computed the noise in graphene‐SiC IMPATT. The noise performance of graphene‐SiC IMPATT is evaluated at Ka band which ranges from 26.5 to 40 GHz. The obtained noise from graphene‐SiC IMPATT is in good agreement with earlier reported noise behavior in IMPATT. We observed that the graphene‐SiC IMPATT is giving the better noise performance in terms of lower computed noise and noise spectral density as compared to other materials reported so far.